Identifikasi dan Pengendalian Risiko K3 pada Proses Produksi CPO dengan Metode HIRARC - Ihsan, Taufiq; Sajidah, Hana; Edwin, Tivany; Derosya, Vioni (LPPM Hang Tuah Pekanbaru, 2025)
Production processes in the palm oil industry pose hazards and risks of occupational accidents. PT XYZ's Palm Oil Mill (POM) unit recorded 15 accident cases in 2021-2023. This study aimed to identify occupational health and safety (OHS) hazards and assess risks at each stage of CPO production at PT XYZ's POM unit using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. This study involved all workers at PT XYZ's POM unit. Primary data were collected through field observations and questionnaires, while secondary data were obtained from company documents. Data analysis included descriptive analysis and risk assessment using the HIRARC method. There were significant differences in risk levels between units. The Loading Ramp had the highest risk due to the intensity of activities, work at height, and heavy equipment movement. The Sorting, Sterilizer, Thresher and Digester, Press, Clarification, and Kernel units had medium risk, while the Weighbridge had the lowest risk. Human factors were the dominant cause of occupational accidents. Risk control recommendations were formulated based on the hierarchy of controls, including elimination, substitution, engineering controls, administrative controls, and the use of Personal Protective Equipment (PPE).